The rule of law between justice and mere legality: A brief overview of the development of discourse in the concept of the rule of law - Nurkić Benjamin; Hasanović Faris (Anali Pravnog Fakulteta u Beogradu)
The rule of law is one of the key concepts in the 21st century. The idea of the rule of law exists to the extent that there are reflections on the state and law, and a relationship between these two concepts. The aim of this paper is to show in one place the development of the idea of the rule of law through history. In this sense, the authors look at the thoughts of philosophers who have largely determined the direction of development of the idea of the rule of law. Of course, not all philosophers who have contemplated the rule of law are listed in the paper, but it nevertheless attempts to show in chronological order how the rule of law as an idea developed from Plato to its modern theorists.